Neo-Liberalism in the Italian University: Encroachment and Resistance. (June 2017) - Scacchi, Luca; Benozzo, Angelo; Carbone, Domenico; Monaci, Maria Grazia
Neo-liberalism has spread throughout the world in tandem with globalization. This article attempts to address the way in which neo-liberalism has operated in the Italian university system, an academic context that has its own history, values, and traditions. A brief overview of the consequences of neo-liberalism in Italy is followed by a description of the stages in the neo-liberal university reforms that have characterized the Italian academic world since the end of the 1980s. Finally, three forms of resistance that hinder the process of neo-liberalization and make it non-linear are examined in depth.